If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 9y = 5y + 4 Reorder the terms: 4 + 9y = 4 + 5y Add '-4' to each side of the equation. 4 + -4 + 9y = 4 + -4 + 5y Combine like terms: 4 + -4 = 0 0 + 9y = 4 + -4 + 5y 9y = 4 + -4 + 5y Combine like terms: 4 + -4 = 0 9y = 0 + 5y 9y = 5y Solving 9y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 9y + -5y = 5y + -5y Combine like terms: 9y + -5y = 4y 4y = 5y + -5y Combine like terms: 5y + -5y = 0 4y = 0 Divide each side by '4'. y = 0 Simplifying y = 0
| 4w^2+8w-3=0 | | 2x+14-4x=28-x | | Y=5sin(4x-3t)WhenY | | 12r^2-20rs+15rs-25s^2= | | xy*9(y*6)+2=98 | | -4.6x=-11 | | -3+2x=x-2 | | -2x+y=45 | | findRE=IR | | findre=i | | 19x-(-6x)=50 | | -49-(-39)=x/9 | | 9r-6r+6=8r+6-r | | 6x+14=7x+9 | | 2,640/k=11 | | (1.8x)+32=x | | 0.6+a=-24 | | 88+x=188 | | 10(x-1)-7=x | | 12-n=n+6 | | 1+2n+5=-6 | | 3(x)-7(x)= | | 6-2x=6x+10x-20 | | 3-2a-1=-6 | | 2r+1=15 | | (4x+3)*(8-3x)=-2x*(6x-2) | | -2-b=-3b+3b | | (3x)x(4x)x(-2x)= | | 3w=2w+15 | | n+2+5=13 | | 8+9(2)=34 | | 4x+3+7x+8+5x+19=180 |